Analysis and Evaluation of SIDUN Mobile Application in UEQ-Based User Experience Perspective - Wulandari, Dewa Ayu Putri (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
This study analyzes and evaluates the user experience (UX) of SIDUN, a mobile-based Village Information System designed to manage community contributions digitally in Dusun Tegal Kori Kaja, Denpasar, Bali. The system aims to address limitations of the previous manual process by enabling digital interaction among villagers, pecalang, and administrative staff. The evaluation method applies the User Experience Questionnaire (UEQ), assessing six core dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. A total of 30 active users participated in the study by completing the UEQ instrument. The results indicate that all six UX dimensions received positive scores, ranging from 1.58 to 2.00. The highest ratings were observed in Stimulation (2.00), Attractiveness (1.96), and Efficiency (1.92), reflecting high user engagement, visual appeal, and operational speed. Perspicuity and Novelty also showed strong performance, while Dependability, though positive, revealed opportunities for improvement in system reliability and consistency. Compared to the UEQ benchmark, all dimensions achieved “Excellent” ratings, placing them within the top 10% of evaluated applications. These findings affirm that SIDUN offers a satisfying user experience and supports effective community-level digital transformation. The study underscores the value of user-centered design and continuous UX assessment in enhancing public digital services in rural communities.